PERAN PROBLEM BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN MICROSOFT OFFICE STUDI KASUS KELAS X SMA NEGERI 2 BENGKULU UTARA - Feronika, Sinda; Yul, Fadlul Amdhi; Selviani, Diah (Jurnal Citra Pendidikan, 2025)
This study aims to investigate the improvement of the understanding and skills of class X students at SMA Negeri 2 North Bengkulu in using Microsoft Office after the application of the Problem Based Learning (PBL) method. The problem faced is the low understanding of the software by students due to the skill gap and passive traditional learning methods. This study uses a qualitative approach with a case study type, involving 75 students from classes X.1 and X.2 who were selected through a saturated sampling technique. Data were collected through observations, interviews, and questionnaires before and after the implementation of PBL. The results showed that the average students' comprehension scores increased from 45% to 81% after the implementation of PBL, which indicates the effectiveness of the method in improving students' skills. The application of PBL not only improves theoretical understanding, but also creates an active and collaborative learning atmosphere. This study recommends further evaluation of the effectiveness of PBL in a broader context and in other subjects.